ChemInform Abstract: Asymmetric Synthesis of Hydrocarbazoles Catalyzed by an Octahedral Chiral‐at‐Rhodium Lewis Acid. Issue 15 (24th March 2016) - Huang, Yong; Song, Liangliang; Gong, Lei; Meggers, Eric
Abstract: A bis‐cyclometalated chiral‐at‐metal rhodium complex catalyzes the Diels—Alder reaction between N‐Boc‐protected 3‐vinylindoles and β‐carboxylic ester‐substituted α, β‐unsaturated 2‐acyl imidazoles with excellent selectivities under optimized conditions.